The Effect of Injection Needle Gauge Size on the Viability of Equine Mesenchymal Stem Cells. (9th September 2013) - Cree, S.J.; Smith, R.K.; Dudhia, J.
Abstract : Aims: Performance horses are at high risk of injury to the superficial digital flexor tendon (SDFT). Studies have shown that autologous mesenchymal stem cells (MSCs) injected into SDFT lesions subsequently result in a significant reduction of re‐injury in National Hunt racehorses; however, recent studies show that only 25% of implanted MSCs survive 24 h post injection. The reason for this loss is unclear but may relate to cell quiescence or injection‐related mortality. We hypothesised that cell viability and mortality is increased with needle gauge. Methods: Equine MSCs cultured in vitro were resuspended to a final suspension density of 5 x 10 5 cells/ml to mimic that used for implantation in clinic. The cell suspension was injected through a 19 gauge, 21 gauge (current practice in clinic) or 23 gauge needle. Mesenchymal stem cells viability and mortality was analysed over a 24 h period post injection using alamarBlue® and Annexin V (apoptosis) assays, respectively. Results: There was a 25% reduction in viability (P<0.01) and mortality (P<0.01) compared with noninjected MSCs over the 24 h period post injection. All needle gauges also induced a decrease in cell metabolic activity immediately post injection but with recovery by 2 h post injection. Furthermore, 21 gauge and 23 gauge needles increased early apoptotic cells immediately post injection, whereas the 19 gauge needle showed a delayed increase in apoptosis until 2 h post injection. Conclusions: The delayed apoptosis may correlate with a subpopulation of quiescent cells subsequently becoming apoptotic. The proportion of early and late apoptotic MSCs, while significant, does not account for the total cell loss reported after intra‐lesional injection. Practical significance: Needle gauge selection has significant implications for the survival of MSC intra‐lesional injections but it may not be the sole factor implicated in post injection cell mortality. We therefore recommend a minimum diameter of 19 gauge should be used for implantation. Ethical animal research: Stem cell lines were obtained from bone marrow with approval of the Institutional Ethical Committee and under UK Home Office licence.Sources of funding: Funded by the Medical Research Council and The Royal Veterinary College.Competing interests: None.